Some propagation methods for cloning holm oak (Quercus ilex L.) plants - Liñán, Juana; Cantos, Manuel; Troncoso, Javier; García, José L.; Fernández, Antonio; Troncoso, Antonio (Central European Journal of Biology, 2011)
Holm oak (Quercus ilex L.), a typical evergreen tree of the Mediterranean area, is very important due to its ecological and economical values. Propagation of this species is extremely difficult and traditionally carried out only by seed germination. In this work, mature acorns were germinated in vitro and in peat substrate in aseptic and non-aseptic conditions. Explants from the seedlings obtained were propagated in vitro in WPM plus 4 µM BA. Plant regeneration was achieved from hypocotyls and root segments cultured in vitro on modified Gamborg medium plus 20 µM BA and 20 µM NAA. 13.8% of the hypocotyls and approximately 30% of the root segments developed both shoots and roots after 30 days of culture. Rooting of stem segments was obtained both in vitro and ex vitro by basal dipping in IBA solutions. Within ex vitro rooting, mother plant age had major influence on the percentage of rooting of the cuttings as the younger plants showed higher ability to root. In this way, Q. ilex plants could be propagated and cloned. The procedure described here would be a very useful tool for breeding programs since vegetative propagation of selected individuals can be achieved.
Keywords: Holm oak; in vitro; plant regeneration; Quercus ilex; rooting; seed germination

Some propagation methods for cloning holm oak (Quercus ilex L.) plants - Liñán, Juana; Cantos, Manuel; Troncoso, Javier; García, José L; Fernández, Antonio; Troncoso, Antonio (Central European Journal of Biology, 2011)
Holm oak (Quercus ilex L.), a typical evergreen tree of the Mediterranean area, is very important due to its ecological and economical values. Propagation of this species is extremely difficult and traditionally carried out only by seed germination. In this work, mature acorns were germinated in vitro and in peat substrate in aseptic and non-aseptic conditions. Explants from the seedlings obtained were propagated in vitro in WPM plus 4 µM BA. Plant regeneration was achieved from hypocotyls and root segments cultured in vitro on modified Gamborg medium plus 20 µM BA and 20 µM NAA. 13.8% of the hypocotyls and approximately 30% of the root segments developed both shoots and roots after 30 days of culture. Rooting of stem segments was obtained both in vitro and ex vitro by basal dipping in IBA solutions. Within ex vitro rooting, mother plant age had major influence on the percentage of rooting of the cuttings as the younger plants showed higher ability to root. In this way, Q. ilex plants could be propagated and cloned. The procedure described here would be a very useful tool for breeding programs since vegetative propagation of selected individuals can be achieved.
Keywords: Holm oak; in vitro; plant regeneration; Quercus ilex; rooting; seed germination